Phosphine resistance, respiration rate and fitness consequences in stored-product insects - Pimentel, Marco Aurélio G; Faroni, Lêda Rita D'A; Tótola, Marcos R; Guedes, Raul Narciso C (Pest Management Science, 2007)
Resistance to fumigants has been frequently reported in insect pests of stored products and is one of the obstacles in controlling these pests. The authors studied phosphine resistance and its physiological basis in adult insects of 12 populations of Tribolium castaneum (Herbst) (Tenebrionidae), ten populations of Rhyzopertha dominica (F.) (Bostrichidae) and eight populations of Oryzaephilus surinamensis L. (Silvanidae) from Brazil, and the possible existence of fitness costs associated with phosphine resistance in the absence of this fumigant. The bioassays for the detection of phosphine resistance followed the FAO standard method. The production of carbon dioxide and the instantaneous rate of population increase (r i ) of each population of each species were correlated with their resistance ratios at the LC 50 . The resistance ratio at LC 50 in T. castaneum ranged from 1.0- to 186.2-fold, in R. dominica from 2.0- to 71.0-fold and in O. surinamensis from 1.9- to 32.2-fold. Ten populations of T. castaneum, nine populations of R. dominica and seven populations of O. surinamensis were resistant to phosphine. In all three species there was significant association (P < 0.05) between respiration rate and phosphine resistance. The populations with lower carbon dioxide production showed a higher resistance ratio, suggesting that the lower respiration rate is the physiological basis of phosphine resistance by reducing the fumigant uptake in the resistant insects. Conversely, populations with higher r i showed lower resistance ratios, which could indicate a lower rate of reproduction of the resistant populations compared with susceptible populations. Thus, management strategies based on the interruption of phosphine fumigation may result in reestablishment of susceptibility, and shows good potential for more effective management of phosphine-resistant populations.
Keywords: Tribolium castaneum; Rhyzopertha dominica; Oryzaephilus surinamensis; Fumigant resistance; Carbon dioxide production; Rate of population growth